2022
DOI: 10.32620/aktt.2022.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Анализ Работы Опорных Подшипников Турбомашин На Экологически Чистых Жидкостях

Abstract: The subject of study in this article is the cost-effectiveness of the rotors of powerful turbines and their fire safety. Improvement of these indicators is possible by replacing oil lubrication systems with environmentally adaptive lubricants (EAL), in particular water or aqueous solutions. The main disadvantage of using water and other low-viscosity aqueous solutions for operating plain bearings is the lack of a hydrodynamic effect at low speeds of the rotor during start and stop of the turbine. The current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Based on the Navier-Stokes equation, Wang et al [57] analyzed the characteristics of the flow field under different speeds and inlet pressures and concluded that increasing the positive pressure zone and decreasing the negative pressure zone increased the opening force of the seal end face and the stiffness of the film, thereby improving its stability. Dotsenko et al [58] experimentally determined the stability parameters of the dry gas seal under different working conditions, which provided a reference for the coordinated optimization of the seal face structure under fluctuating working conditions in the later stage. Hu et al [59] analyzed the influence of different speeds, pressures, and temperatures on the steady-state performance of the dry gas seal and on the leakage and friction power consumption.…”
Section: Effects Of Operating Parametersmentioning
confidence: 99%
“…Based on the Navier-Stokes equation, Wang et al [57] analyzed the characteristics of the flow field under different speeds and inlet pressures and concluded that increasing the positive pressure zone and decreasing the negative pressure zone increased the opening force of the seal end face and the stiffness of the film, thereby improving its stability. Dotsenko et al [58] experimentally determined the stability parameters of the dry gas seal under different working conditions, which provided a reference for the coordinated optimization of the seal face structure under fluctuating working conditions in the later stage. Hu et al [59] analyzed the influence of different speeds, pressures, and temperatures on the steady-state performance of the dry gas seal and on the leakage and friction power consumption.…”
Section: Effects Of Operating Parametersmentioning
confidence: 99%